Seções de choque da interação de elétrons de energias intermediárias com moléculas poliatômicas e constituintes do DNA - Sugohara, Renato Takeshi (Universidade Federal de São Carlos, 2012)
Elastic Differential Cross Sections (EDCS) were measured for the interaction of electrons in the incident energy range of 100-1000 eV, with several polyatomic molecules, namely: ethane (C2H6), propane (C3H8), methanol (CH3OH), ethanol (C2H5OH), sulfur dioxide (SO2), tetramethylsilane - TMS (C4H12Si), tetrahydrofuran - THF (C4H8O), trimethylphosphate - TMP (C3H9O4P) and ethyl acetate (C4H8O2). Crossed beam geometry is used and the intensities of elastically scattered electrons selected by a retarding field analyzer are measured as function of the scattering angles. The covered angular range is from 5to 130and the relative flow technique is used to normalize experimental scattered intensities to absolute scale. The secondary standards are Ar and N2. Only for TMP the normalization to absolute scale relied on theoretical values calculated with the Independent Atom Model (IAM). The EDCS curve was manually extrapolated to generate data in the forward and backward directions that were not covered experimentally. The full curve of EDCS from 0º to 180º was then integrated to give the Integral Elastic Cross Sections (IECS) and Momentum Transfer Cross Section (MTCS) in the 100 1000 eV interval. Part of results of this study has already appeared in scientific articles in the specialized literature. The results are new for TMP and ethyl acetate. The present experimental values of EDCS, IECS and MTCS are reported in comparison with available data. There was no experimental data in the literature to be compared with our measurements, in the 200 1000 eV except for THF. The theoretical data used for comparison are based on the Schwinger Variational Iterative Method (SVIM) and the Pade Approximant with the computer code EpolyScatD. In addition, the IAM and the Additivity Rule (AR) were also used to generate theoretical EDCS values. In general, a good agreement was seen between theoretical and experimental values. This study points out the importance of inclusion of the absorption effects in the optical potential, especially for intermediate energy electrons and scattering angles above 20º.
Keywords: Espalhamento (Fisica); Alcool; Tetrahidrofurano; CIENCIAS EXATAS E DA TERRA::FISICA